KEPUASAN MUSTAHIK TERHADAP PENYALURAN DAN MANFAAT ZAKAT UNTUK MODAL USAHA DI KOTA BENGKULU - Muhamad Abduh; Effed Darta (AKUNTABILITAS, 2020)
This research aims to: a) investigate the perceptions of zakat recipients (mustahik) regarding the distribution mechanism and benefits of zakat for business capital and b) assess the level of mustahiks' satisfaction with the mechanism and benefits of the zakat. The research used primary data collected from 60 mustahiks using a questionnaire and then analizedusing a descriptive method and SatMat analysis tool (Satisfaction Matrix) developed by Abduh et al (2007) to assess the level of mustahiks' satisfaction. The results showed that the majority of respondents perceived that the zakat for the business capital they received had the expected benefits (such as the creation of opportunities to open their own businesses and increase income) and they were satisfied with the procedures and mechanism of channeling zakat for the business capital. In order to increase the effectiveness of the venture capital zakat, they hope that more coaching will be given to develop the business (such as financial management, product development and marketing